Electron–hole recombination dynamics in carbon nanodots. (December 2015) - Nguyen, Vanthan; Si, Jinhai; Yan, Lihe; Hou, Xun
Abstract: Since their discovery, carbon nanodots (C-dots) have attracted great interest due to their strong photoluminescence (PL). Yet a full understanding of the mechanisms for PL from C-dots is still under debate. In this work, we analyzed the evolution of the time-resolved PL spectra of C-dots using picosecond time-resolved spectroscopy to explore the carrier dynamics in C-dots. Our results suggest two different pathways of electron–hole radiative recombination, each with distinct relaxation time scales: a relaxation of carriers from carbogenic core onto the surface states with a slow decay (>14 ns) and direct radiative recombination of carriers on the surface states with a fast decay (∼1.3 ns). The slow decay at short-wavelength emissions is dominant due to the effective relaxation from the carbogenic core onto the surface states, while the fast decay is dominant at long-wavelength emissions. An explanation for the excitation-dependent and independent PL properties of C-dots is also presented here using this carrier dynamic model.